Some reflections on the power to/power over debate. Issue 3 (2nd September 2017) - Battegazzorre, Francesco
Abstract: Among the most prominent and interesting issues discussed by students of power is the conceptual divide between power to and power over . The discussion of this topic has been revived in an exchange between Pamela Pansardi and Peter Morriss hosted in the pages of the Journal of Political Power . Pansardi defended a strong position which involved denying the usefulness – if not the logical possibility – of distinguishing between power to and power over . In his reply, Morriss defended the distinction by pointing out a pertinence argument in support of his own favoured way of distinguishing between the two concepts. Unfortunately, the exchange between the two authors was inconclusive. In this paper, I discuss the merits and limits of the two proposals and I put forward an intermediate position which, I hope, adds some clarity to the debate over the two conceptions of power.